2023
DOI: 10.1177/03635465231177054
|View full text |Cite
|
Sign up to set email alerts
|

Use of Publicly Obtained Data in Sports Medicine Research: A Systematic Review and Bibliometric Analysis

Abstract: Background: Publicly obtained data (POD) have recently been utilized frequently by sports medicine researchers to describe injury patterns, risk factors, and outcomes in elite athletes. The relative ease of this type of research that is based solely on internet and media sources has resulted in a near exponential increase in the number of these POD studies. Purpose: To systematically review the sports medicine literature for studies based solely on POD. Study Design: Systematic review and bibliometric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The current study provides meaningful findings, considering the prevalence of research reports that disseminate results based on analyses using publicly available data. In fact, a recent systematic review and bibliometric analysis identified an exponential increase in manuscripts using this methodology (Inclan et al 2023b ). One example is a recent research report that identified no increased risk of subsequent musculoskeletal injury after sustaining SRC in NFL players (Buckley et al 2022 ), which were in contrast to findings reported at other levels of participation (Lynall et al 2017 ; Nusbickel et al 2022 ; Herman et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study provides meaningful findings, considering the prevalence of research reports that disseminate results based on analyses using publicly available data. In fact, a recent systematic review and bibliometric analysis identified an exponential increase in manuscripts using this methodology (Inclan et al 2023b ). One example is a recent research report that identified no increased risk of subsequent musculoskeletal injury after sustaining SRC in NFL players (Buckley et al 2022 ), which were in contrast to findings reported at other levels of participation (Lynall et al 2017 ; Nusbickel et al 2022 ; Herman et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Subsequently, between 2003 and February 2022, a total of 209 studies were published using publicly obtained injury data, including 25 studies in the American Journal of Sports Medicine. 6 The strength of publicly obtained datasets is availability. Every researcher has the freedom and the access to study novel ideas.…”
Section: Editorialmentioning
confidence: 99%
“…Publicly obtained dataset studies use publicly available injury reports in print or online media. 6 These studies typically involve athletes at the professional, semiprofessional, or collegiate level. Common sources cited include game summaries, weekly injury reports, player profiles, and play-by-play documents that are found on team-specific websites, league websites, fantasy sports websites, and popular mainstream media.…”
mentioning
confidence: 99%
See 1 more Smart Citation